Risk Factors Associated with the Incidence of Dengue Hemorrhagic Fever (DHF) in the Kenali Besar Health Center Work Area of Jambi City in 2025 - Herlin Febria Sari; Oka Lesmana S; Fajrina Hidayati; Rd. Halim; Hendra Dhermawan Sitanggang (International Journal of Health Engineering and Technology, 2025)
The number of DHF cases in the Kenali Besar Besar Health Center, Jambi City continues to increase every year. This study aims to determine the risk factors associated with the incidence of dengue hemorrhagic fever (DHF) in the Kenali Besar Health Center, Jambi City. The design of this study was a Case Control design. The population in this study was the total number of DHF cases in the period January 2024-March 2025. These respondents were divided into two groups, namely the total sample was 93 consisting of 31 cases and 62 controls or 1: 2. Sampling of cases and controls using non-probability sampling or purposive sampling techniques. Analysis was carried out using the Chi-square test. The results of the study showed that the independent variables associated with DHF include; PSN 3M practice (p-value = 0.006 and OR = 3.870) the presence of mosquito larvae (p-value = 0.006 and OR = 3.870), residential density (p-value = 0.015 and OR = 3.385), the habit of hanging clothes (p-value = 0.030 and OR = 3.214), Water Reservoirs (p-value = 0.002 and OR = 4.747) are related to the incidence of Dengue Hemorrhagic Fever (DHF).  Risk factors related to the incidence of DHF are the Implementation of 3M Practices, the presence of mosquito larvae, residential density, the habit of hanging clothes and water reservoirs with the incidence of DHF. It is hoped that the community can take action to eradicate mosquito nests in the home environment and the surrounding environment so that there is no place for aedes aegypti mosquitoes to breed.